### (7x^2-2x+16)+(6x^2+8x-46)

This faces simplification or other simple results.

## Step by step Solution

## Step 1 :

Equation at the finish of step 1 : (((7•(x2))-2x)+16)+(((2•3x2)+8x)-46)## action 2 :

Equation at the end of action 2 : ((7x2 - 2x) + 16) + (6x2 + 8x - 46)## Step 3 :

Trying to factor by splitting the center term3.1Factoring 13x2+6x-30 The very first term is, 13x2 the coefficient is 13.The middle term is, +6x its coefficient is 6.The critical term, "the constant", is -30Step-1 : main point the coefficient of the very first term by the continuous 13•-30=-390Step-2 : discover two determinants of -390 whose sum equals the coefficient that the middle term, which is 6.-390 | + | 1 | = | -389 | ||

-195 | + | 2 | = | -193 | ||

-130 | + | 3 | = | -127 | ||

-78 | + | 5 | = | -73 | ||

-65 | + | 6 | = | -59 | ||

-39 | + | 10 | = | -29 | ||

-30 | + | 13 | = | -17 | ||

-26 | + | 15 | = | -11 | ||

-15 | + | 26 | = | 11 | ||

-13 | + | 30 | = | 17 | ||

-10 | + | 39 | = | 29 | ||

-6 | + | 65 | = | 59 | ||

-5 | + | 78 | = | 73 | ||

-3 | + | 130 | = | 127 | ||

-2 | + | 195 | = | 193 | ||

-1 | + | 390 | = | 389 |

Observation : No two such factors can be discovered !! Conclusion : Trinomial deserve to not be factored